2009
DOI: 10.3233/ves-2008-185-601
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of visual field dependence: Comparison between the mechanical 3D rod-and-frame test developed by Oltman in 1968 with a 2D computer-based version

Abstract: The identification of subject’s perceptual style regarding multisensory integration is a central issue for spatial perception and sensorimotricity. In spatial orientation studies, the weighting of visual frame of reference (visual field dependence) is classically assessed by using verticality perception tasks, and especially the mechanical 3D rod-and-frame test (3D RFT). The validation of a 2D computer-based version of the RFT by virtue of its portability would facilitate the identification of modes of spatial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(4 citation statements)
references
References 47 publications
1
3
0
Order By: Relevance
“…The average bias on the RFT in the non-tilted condition was less than 1°, typical of conditions without a frame or with a non-tilted frame in healthy participants [ 19 21 ]. The average error found for the tilted frame conditions, 3.65°, was similar in magnitude to what others have found in 3D virtual and real RFTs, ranging from 3° to 5° in young adults (e.g., [ 10 , 13 , 22 ]). Further, we replicated the well-known finding in the literature that women were slightly (but with statistical significance) more influenced than men by the tilted frame in judging the rod’s orientation.…”
Section: Discussionsupporting
confidence: 86%
“…The average bias on the RFT in the non-tilted condition was less than 1°, typical of conditions without a frame or with a non-tilted frame in healthy participants [ 19 21 ]. The average error found for the tilted frame conditions, 3.65°, was similar in magnitude to what others have found in 3D virtual and real RFTs, ranging from 3° to 5° in young adults (e.g., [ 10 , 13 , 22 ]). Further, we replicated the well-known finding in the literature that women were slightly (but with statistical significance) more influenced than men by the tilted frame in judging the rod’s orientation.…”
Section: Discussionsupporting
confidence: 86%
“…Visual field dependence is considered as the level of reliance on visual cues in comparison to body-based cues 15,16 . A popular way to evaluate it is using the rod and frame test 10,[17][18][19] . Visual field dependency varies across healthy people 20,21 , and was found to be higher in individuals with pathologic or physiologic (e.g., aging) balance related conditions [22][23][24][25][26] .…”
Section: Introductionmentioning
confidence: 99%
“…The most used methods to analyze the perception of visual verticality (VV) in clinical practice and research is the Subjective Visual Vertical (SVV) test [14], which provides information on the contribution of the vestibular system to the perception of VV. Likewise, the Rod and Frame Test (RFT) [15] assesses the contribution of the visual system to the perception of VV at the same time that it classifies the subjects as visually dependent or independent. Recent studies have reported that FMS patients appear to have poor vestibular and visual scores in balances tests and showed that static balance and gait during unsteadiness conditions with open or closed eyes are significantly worse in FMS patients and older adults than in healthy subjects [16].…”
Section: Introductionmentioning
confidence: 99%